Aplikasi Social Learning Networks Berbasis Web (Studi Kasus Di STMIK Mardira Indonesia) - Dadi Rosadi (STMIK Mardira Indonesia, Bandung, 2016)
This research aims to create applications that can improve the quality, effectiveness, ease of use and the use of learning media Virtual Class with an interesting learning concept is Social Learning Networks (SLN) web-based. SLN itself a slice of the merger between the Social Network (SN) with E-Learning or Virtual Class. This application can be applied in college STMIK MARDIRA INDONESIA, given the college has facilities infrastructure in the field of information technology (IT) support. With the implemented application is expected to overcome a problem that is common for students and lecturers. Research methodologies were used in this research is descriptive analysis research methodology of data collection techniques include Literature Study, observation, interview. While the system development method used is the method with object-oriented modeling UML (Unified Modeling Language). Stages in the methodology used including Preliminary Investigation, Requirements Analysis, System Design, Coding and Testing, and Implementation (Implementation). Keywords: social learning networks, e-learning, virtual class.